Development of Vegetarian Thai Cuisine Standard Recipes to Promote the Dissemination of Thai Cuisine Standards for Non-Meat Consumers - Promchan, Nutthawut; Sriwannawit, Chanika; Phiriyaphorn, Phatchara; Suwannachot, Nikorn; Muangsomboon, Satit; Niyomwong, Kanittha; Boonchauycho, Akkapol; Runghairun, Pimchanok; Rugmai, Siripong; Mayuree, Wacharakorn; Sakkaekaew, Korawit (Dusit Thani College Journal, 2025)
This research aimed to develop a standard recipe for vegetarian Thai cuisine and present a guideline for disseminating the standard recipe of vegetarian Thai cuisine for vegetarians. Literature review of recipes and cooking method were performed in order to select the menu for standard recipe for vegetarian Thai cuisine. Then, experimented with cooking until they obtaining an appropriate standard recipe for vegetarian Thai cuisine. In addition, the nutritive value per serving of each item was calculated. The research results were able to develop a total of 35 standard recipes for vegetarian Thai cuisine, consisting of 5 snacks, 20 savory dishes, and 10 sweet dishes, such as vegetarian deep-fried chicken wrapped in pandanus leaves, vegetarian beef massaman curry, vegetarian red curry with roast duck, vegetarian chicken green curry, grain pudding with young coconut, poached pumpkin in coconut milk, mango with sticky rice, and vegetarian coconut flavored sticky rice with dried fish and sugar. The research results on the guidelines for disseminating the standard recipe for vegetarian Thai cuisine can be developed into a book of standard recipes for vegetarian Thai cuisine. This cook book should contain information about Thai cuisine and vegetarian cuisine, origins, concepts, and conduct of research; information about vegetarian Thai cuisine cooking process, ingredients, and seasonings; and a list of vegetarian Thai cuisine items, including pictures, ingredients (recipes), methods of preparation, nutritive values per serving and observed special remards on cooking.